Evaluation of the ultrasound reproducibility as a method to measure the subcutaneous tissue of the nasal tip - Naves, Marcell de Melo; Sousa, Rogério Costa; Tomé, Raphael Alves Ferreira; Damian, Nicholas Godoy Canazza; Diniz, Angélica Lemos Debs; Patrocinio, Lucas Gomes (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The previous evaluation of the patient's anatomy is crucial to achieve a sharp nasal tip in a rhinoplasty. The thickness of the subcutaneous tissue is indispensable for the esthetical harmony of the area. Techniques to measure such structures on the patient 'in vivo' are not found in literature.Objective: Evaluate the inter-observer inconsistency of the ultrasound method to measure the thickness of the subcutaneous tissue of the nasal tip by way of an ultrasound.Method: 47 volunteers were submitted to a nasal tip ultrasound performed by two radiology specialists, who used the same exam technique with a linear electronic transducer at a frequency between 5 and 9 MHz. The thickness of the subcutaneous tissue was evaluated by measuring the point with the highest protrusion of the largest alar cartilage dome towards skin. Prospective study.Results: The measurement averages of the subcutaneous tissue of the nasal tip achieved by the examiners did not show statistically significant differences (p = 0.5303). When analyzing the reproducibility between examiners, an interclass 'r'correlation coefficient (Pearson) 0.9333, i.e., an excellent inter-observer reproducibility was found.Conclusion: The ultrasound proved to be reproducible and examiners satisfactorily agree about evaluating the thickness of the subcutaneous tissue of the skin, thus helping the surgeon perform the pre-surgical analysis and find the best surgical technique for each case.
Keywords: rhinoplasty; nasal cartilages; ultrasound